Head-to-head comparison of fibroblast activation protein inhibitors (FAPI) radiopharmaceuticals and [18F]FDG in gynaecological malignancies: systematic literature review and meta-analysis. - Florit, Anita; de Koster, Elizabeth J.; Sassano, Serena; Alic, Lejla; Pisano, Giusi; van Velden, Floris H. P.; Annunziata, Salvatore; Primac, Irina; Ruggiero, Maria Rosaria; Müller, Cristina; Sala, Evis; Fendler, Wolfgang P.; et al. (European Journal of Nuclear Medicine & Molecular Imaging, 2025)
Purpose: This study aims to systematically review and perform a meta-analysis to compare the diagnostic performance of fibroblast activation protein inhibitors (FAPI) radiopharmaceuticals and 2-deoxy-2-[18F]fluoro-D-glucose ([18F]FDG) in gynaecological cancers. Methods: A comprehensive search of PubMed/MEDLINE and EMBASE was conducted and updated to October 25, 2024, to identify clinical studies evaluating FAPI and [18F]FDG PET/CT or PET/MR in patients with gynaecological cancer. Quality was assessed using the QUADAS-2 tool (Quality Assessment of Diagnostic Accuracy Studies). Per-lesion pooled estimates of sensitivity, specificity, positive predictive value, and negative predictive value were calculated with 95% confidence intervals. Results: Ten studies were included for qualitative assessment and five studies focusing on ovarian cancer were included in the meta-analysis. The detection rates of primary cervical cancer ranged from 96 to 100% for both radiopharmaceuticals. For the primary tumour in ovarian cancer, the pooled sensitivities of 68Ga-FAPI and [18F]FDG were 95% and 92%, and the pooled specificities were 81% for both radiopharmaceuticals. Nodal metastases detection was higher with 68Ga-FAPI compared with [18F]FDG in cervical cancer. Similarly, in ovarian cancer the estimated pooled sensitivities of 68Ga-FAPI and [18F]FDG were 97% and 88%, and the pooled specificities were 83% and 41%, respectively. At peritoneal metastases analysis in ovarian cancer, the pooled sensitivities of 68Ga-FAPI and [18F]FDG were 97% and 70%, and the pooled specificities were 93% and 88%, respectively. At the visual assessment of peritoneal cancer scores, such as peritoneal cancer index, 68Ga-FAPI detected a greater tumour burden compared with [18F]FDG. A comparative analysis of the PET semiquantitative parameters was also performed. Conclusion: Despite limited literature data, radiopharmaceuticals based on FAPIs are a promising alternative to [18F]FDG for imaging gynaecological cancers, in particular for the detection of nodal metastases in cervical and ovarian cancers, as well as for detecting peritoneal metastases in ovarian cancers. Larger prospective studies are needed to confirm these results and promote the inclusion of FAPI radiopharmaceuticals in clinical practice. Clinical trial number: Not applicable.